Re‐evaluation of lecithins (E 322) as a food additive - EFSA Panel on Food Additives and Nutrient Sources added to Food (ANS) (EFSA Journal, 2017)
Abstract The present opinion deals with the re‐evaluation of lecithins (E 322) when used as a food additive. Lecithins (E 322) is an authorised food additive in the EU according to Annex II and Annex III to Regulation (EC) No 1333/2008 on food additives, and have been previously evaluated by JECFA in 1973 and by the SCF in 1982. Among lecithins, phosphatidylcholine is hydrolysed in choline in the cytidine‐5‐diphosphate‐choline pathway in all cells of the body. Following the conceptual framework for the risk assessment of certain food additives re‐evaluated under Commission Regulation (EU) No 257/2010, the Panel concluded that there was no need for a numerical ADI for lecithins (E 322) and that there was no safety concern for the general population from more than 1 year of age at the refined exposure assessment for the reported uses of lecithins (E 322) as a food additive. The Panel further concluded that there is no safety concern for the exposure to the choline from lecithins (E 322) as a food additive at use and use levels reported by industry. For infants (from 12 weeks up to 11 months of age), the Panel concluded that there was no safety concern at the refined exposure assessment for the reported uses of lecithins (E 322) as a food additive and for the choline from lecithins (E 322) as a food additive at use and use levels reported by industry. For infants and young children consuming foods for special medical purposes, the Panel concluded that there was no safety concern with respect to the refined exposure assessment for the reported uses of lecithins (E 322) as a food additive and for exposure to choline resulting from these uses of lecithins (E 322).